2021
DOI: 10.1186/s12888-021-03185-3
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder and self-esteem: a meta-analysis

Abstract: Objective Body dysmorphic disorder (BDD) is associated with low self-esteem. The aim of this meta-analysis was to examine the strength of the cross-sectional relationship between BDD symptom severity and global self-esteem in individuals with BDD, mentally healthy controls, community or student samples, and cosmetic surgery patients. Moreover, the role of depressive symptom severity in this relationship and other moderating factors were investigated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 68 publications
1
13
0
1
Order By: Relevance
“…Moreover, sub-clinical body dysmorphia shared significantly stronger negative correlations with self-esteem and self-perceived attractiveness than sub-clinical restrictive disordered eating shared with self-esteem and self-perceived attractiveness. The negative correlations between both sub-clinical restrictive disordered eating and sub-clinical body dysmorphia and self-perceived attractiveness and self-esteem are consistent with research showing that both anorexia nervosa (Blechert et al, 2011), and body dysmorphic disorder (Kuck et al, 2021), relate to low levels of self-esteem. The positive correlation between sub-clinical restrictive disordered eating and BIS sensitivity is consistent with previous studies (du Rocher et al, 2021;Wilson et al, 2019), as is the positive correlation between sub-clinical body dysmorphia and BIS sensitivity (Schieber et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, sub-clinical body dysmorphia shared significantly stronger negative correlations with self-esteem and self-perceived attractiveness than sub-clinical restrictive disordered eating shared with self-esteem and self-perceived attractiveness. The negative correlations between both sub-clinical restrictive disordered eating and sub-clinical body dysmorphia and self-perceived attractiveness and self-esteem are consistent with research showing that both anorexia nervosa (Blechert et al, 2011), and body dysmorphic disorder (Kuck et al, 2021), relate to low levels of self-esteem. The positive correlation between sub-clinical restrictive disordered eating and BIS sensitivity is consistent with previous studies (du Rocher et al, 2021;Wilson et al, 2019), as is the positive correlation between sub-clinical body dysmorphia and BIS sensitivity (Schieber et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…For example, body dysmorphic disorder relates to an underestimation of one's own attractiveness (relative to objective observers' ratings; Buhlmann, Etcoff, & Wilhelm, 2008), and anorexia nervosa relates to a belief that a lower body mass index (BMI) is more attractive (Tovee et al, 2000). Both anorexia nervosa (Blechert et al, 2011) and body dysmorphic disorder (Kuck et al, 2021) relate to low levels of self-esteem. Collectively, these studies on the perception of attractiveness and levels of self-esteem suggest that self-appraisals play an important role in the proposed body image disorders.…”
mentioning
confidence: 99%
“…The development of psychiatric conditions, such as BDD, can be influenced by low self-esteem. 35,36 Self-esteem usually increases with age. 36 Bjornsson et al examined the age of BDD's onset and found that individuals who developed BDD early in life had more severe BDD symptoms and a higher risk for other psychiatric conditions including borderline personality disorder, anxiety disorders, suicidal attempts, and psychiatric hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Across modules, AINA pursues the aim of fostering awareness of resources and (re-)defining and enhancing self-esteem. Relatedly, recent meta-analytic evidence revealed a moderately negative relationship between BDD symptoms and self-esteem and suggested that low self-esteem is an important hallmark of BDD beyond the influence of depressive symptoms ( Kuck et al, 2021 ). It seems that individuals with BDD build their self-esteem predominantly on their appearance.…”
Section: Introductionmentioning
confidence: 99%